2016
DOI: 10.4014/jmb.1510.10018
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties and Cytotoxicity of Sulfated (1,3)-��-D-Glucan from the Mycelium of the Mushroom Ganoderma lucidum

Abstract: Ganoderma lucidum BCCM 31549 has a long established role for its therapeutic activities. In this context, much interest has focused on the possible functions of the (1,3)-β-D-glucan (G) produced by these cultures in a stirred-tank bioreactor and extracted from their underutilized mycelium. In the existing study, we report on the systematic production of G, and its sulfated derivative (GS). The aim of this study was to investigate G and its GS from G. lucidum in terms of their antibacterial properties and cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…2 Effect of the Ganoderma lucidum extracts obtained by high-pressure steaming and enzymatic pretreatment on the viability (A) and the migration (B) of B16F10 cells. CON, control; RES, resveratrol (10 lg/mL); NPT, non-pre-treatment; SET, steaming and enzymatic pretreatment; *, **, ***, ****significant difference from the control at t \ 0.1, t \ 0.05, t \ 0.01, t \ 0.001, respectively extract was harmless to the cells, consistent with previous research using human prostate cell [41]. The cell migration on the slit of the confluent wells was photographed after 0, 6, and 12 h in each condition.…”
Section: Resultssupporting
confidence: 86%
“…2 Effect of the Ganoderma lucidum extracts obtained by high-pressure steaming and enzymatic pretreatment on the viability (A) and the migration (B) of B16F10 cells. CON, control; RES, resveratrol (10 lg/mL); NPT, non-pre-treatment; SET, steaming and enzymatic pretreatment; *, **, ***, ****significant difference from the control at t \ 0.1, t \ 0.05, t \ 0.01, t \ 0.001, respectively extract was harmless to the cells, consistent with previous research using human prostate cell [41]. The cell migration on the slit of the confluent wells was photographed after 0, 6, and 12 h in each condition.…”
Section: Resultssupporting
confidence: 86%
“…These authors evaluated the sulfonation of polysaccharides extracted from Cyclocarya paliurusi and found a 63.14% OH radical removal capacity in the sulfonated polysaccharide with DS of 0.25. Scientific reports have indicated that polysaccharides following chemical derivatization by sulfonylation present an increase in antimicrobial capacity [11,23]. This effect was also observed in the present study with sulfonated lasiodiplodan with DS of 0.24 (Table 1), which presented antimicrobial potential against Gram-negative bacteria (E. coli and S. enterica Typhimurium) and the yeasts (C. albicans and C. tropicalis).…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, Zhang et al [34] evaluated the antimicrobial potential of a sulfonated polysaccharide with DS close to 0.24, and also found inhibitory activity against the Gram-negative bacteria (E. coli and S. enterica Typhimurium), suggesting that sulfonation is an effective method to improve the bioactivity of polysaccharides. Similarly, Wan-Mohtar et al [11] observed antimicrobial activity of sulfonated polysaccharides against strains of E. coli and S. enterica Typhimurium evaluating sulfonated polysaccharide concentrations close to those employed in this study.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations